A prospective study of nomogram-based adaptation of prostate radiotherapy target volumes. Issue 1 (December 2015) - Wu, Raymond; Woodford, Hannah; Capp, Anne; Hunter, Perry; Cowin, Gary; Tai, Keen-Hun; Nguyen, Paul; Chong, Peter; Martin, Jarad
Abstract Background A prospective clinical trial was conducted to evaluate the feasibility of a novel approach to the treatment of patients with high risk prostate cancer (HRPC) through the use of a nomogram to tailor radiotherapy target volumes. Methods Twenty seven subjects with HRPC were treated with a mildly hypofractionated radiotherapy regimen using image-guided IMRT technique between Jun/2013-Jan/2015. A set of validated prognostic factors were inputted into the Memorial-Sloan-Kettering Cancer Center (MSKCC) prostate cancer nomogram to estimate risk of loco-regional spread (LRS). The nomogram risk estimates for extra-capsular extension (ECE), seminal vesicles involvement (SVI), and pelvic lymph nodes involvement (LNI) were used to adapt radiotherapy treatment volumes based on a risk threshold of ≥15 % in all cases. A planning guide was used to delineate target volumes and organs at risk (OAR). Up to three dose levels were administered over 28 fractions; 70Gy for gross disease in the prostate +/− seminal vesicles (2.5Gy/fraction), 61.6Gy for subclinical peri-prostatic disease (2.2Gy/fraction) and 50.4Gy to pelvic nodes (1.8Gy/fraction). Data regarding protocol adherence, nomogram use, radiotherapy dose distribution, and acute toxicity were collected. Results Nomogram use 100 % of patients were treated for ECE, 88.9 % for SVI, and 70.4 % for LNI. The three areas at risk of LRS were appropriately treated according to the study protocol in 98.8 % cases. The MSKCC nomogram estimates for LRS differed significantly between the time of recruitment and analysis. Contouring protocol compliance Compliance with the trial contouring protocol for up to seven target volumes was 93.0 % (159/171). Compliance with protocol for small bowel contouring was poor (59.3 %). Dose constraints compliance Compliance with dose constraints for target volumes was 97.4 % (191/196). Compliance with dose constraints for OAR was 88.2 % (285/323). Acute toxicity There were no grade 3 acute toxicities observed. 20/27 (74.1 %) and 6/27 (22.2 %) patients experienced a grade 2 genitourinary and gastrointestinal toxicity respectively. Conclusions We have demonstrated the feasibility of this novel risk-adapted radiation treatment protocol for HRPC. This study has identified key learning points regarding this approach, including the importance of standardization and updating of risk quantification tools, and the utility of an observer to verify their correct use. Trial registration ClincialTrials.gov identifierNCT01418040 . Hunter New England Human Research Ethics Committee (HNEHREC) reference number 12/08/15/4.02